New Data on Human Macrophages Polarization by Hymenolepis diminuta Tapeworm—An In Vitro Study - Zawistowska-Deniziak, Anna; Basałaj, Katarzyna; Strojny, Barbara; Młocicki, Daniel (Frontiers in Immunology, 2017)
Helminths and their products can suppress the host immune response to escape host defence mechanisms and establish chronic infections. Current studies indicate that macrophages play a key role in the immune response to pathogen invasion. They can be polarized into two distinct phenotypes: M1 and M2. The present paper examines the impact of the adult Hymenolepis diminuta tapeworm (HD) and its excretory-secretory products (ESP) on THP-1 macrophages. Monocytes were differentiated into macrophages and cultured with a living parasite or its ESP. Our findings indicate that HD and ESP have a considerable impact on human THP-1 macrophages. Macrophages treated with parasite ESP (with or without LPS) demonstrated reduced expression of cytokines (i.a. IL-1α, TNFα, TGFβ, IL-10) and chemokines (i.a. IL-8, MIP-1α, RANTES, and IL-1ra), while s-ICAM and CxCL10 expression rose after ESP stimulation. In addition, inflammatory factor expression rose significantly when macrophages were exposed to living parasites. Regarding induced and repressed pathways, significant differences were found between HD and ESP concerning their influence on the phosphorylation of ERK1/2, STAT2, STAT3, AMPKα1, Akt 1/2/3 S473, Hsp60 and Hck. The superior immunosuppressive properties of ESP compared to HD were demonstrated with lower levels of IL-1β, TNF-α, IL-6, IL-23 and IL-12p70 following stimulation. The presence of H. diminuta and its ESP were found to stimulate mixed M1/M2 macrophage phenotypes. Our findings indicate new molecular mechanisms involved in the response of human macrophages to tapeworm infection, this could be a valuable tool in understanding the mechanisms underlying the processes of immune regulation during cestodiasis.